Transforming Tanzania’s Cities : Harnessing Urbanization for Competitiveness, Resilience, and Livability - World Bank (World Bank, Washington, DC, 2021)
Tanzania’s growth and poverty reduction aspirations hinge on shifting from a reliance on agriculture toward greater productivity. Cities’ key role in generating a more competitive economy is already apparent: in 2012, just four Tanzanian cities produced more than half of the country’s gross domestic product (GDP), and they are expected to represent almost 60 percent of the country’s GDP in 2030. Urban areas also account for the majority of the country’s physical, financial, human, academic, and technological capital. Cities are integral for shaping Tanzania’s development, but what shape are cities in now and where are they heading based on current trends? This report analyses the state of Tanzania’s urbanization process and the condition of its cities and institutions through the lens of three main challenges that constrain the contribution of Tanzania’s towns and cities to economic diversification and growth, reduce their resilience to shocks, and limit their livability and inclusivity. The report then offers a set of recommendations to guide policies and investments that will promote urban planning for inclusive and resilient urban development, stronger connections between cities and neighborhoods, and institutions and financing mechanisms that are well placed to scale up sustainable urban development.